Identification and Characterization of Quantitative Trait Loci for Shattering in Japonica Rice Landrace Jiucaiqing from Taihu Lake Valley, China. Issue 3 (1st November 2016) - Cheng, Jinping; He, Yongqi; Zhan, Chengfang; Yang, Bin; Xu, Enshun; Zhang, Hongsheng; Wang, Zhoufei
Abstract : Easy shattering reduces yield from grain loss during rice ( Oryza sativa L.) harvest. We characterized a nonshattering japonica rice landrace Jiucaiqing from Taihu Lake valley in China. The breaking tensile strength (BTS; grams force, gf) of the grain pedicel was measured using a digital force gauge to evaluate the degree of shattering at 0, 7, 14, 21, 28, and 35 d after heading (DAH). The BTS of Jiucaiqing did not significantly decrease with increasing DAH, maintaining a level of 152.2 to 195.9 gf, while that of indica IR26 decreased greatly during 0 to 14 DAH and finally stabilized at ∼100 gf. Then the chromosome segment substitution lines (CSSLs) and near isogenic lines (NILs) of Jiucaiqing in IR26 background were developed for quantitative trait loci (QTL) mapping. Four putative QTL ( qSH1 JCQ, qSH3 JCQ, qSH6 JCQ, and qSH11 JCQ ) for shattering were detected, and the qSH1 JCQ was confirmed on chromosome 1. We further mapped qSH1 JCQ to a 98.4‐kb region, which contains 14 genes. Os01g62920 was considered to be a strong candidate for qSH1 JCQ, which colocated with qSH1 . Further quantitative real‐time polymerase chain reaction (PCR) analyses confirmed that the QTL qSH1 JCQ can significantly decrease the expression of shattering related genes ( qSH1, OsCPL1, Sh4, SH5, and SHAT1 ) especially at the middle development stage at 10 and 15 cm panicle length, which causes rice shattering decrease. The elite allele and the NIL with desirable agronomic traits identified in this study could be useful for rice breeding.